Babushka in Riga – Age and Power in Russian-Speaking Translocal Contexts - Novikova, Irina (Sociologija. Mintis ir veiksmas, 2005)
Using a transnational perspective, this article analyzes a web of relations forged by, around and among women in the age of babushka in the Russian-speaking families of Riga, Latvia, and the ways in which gender, age and power interface the relations in the sphere of the private, intimate, familial. My interest is in looking into how these relations position women of age in certain social formations, in the exchanges of material and intangible resources and symbols between their “origins” and their “place”. The object of my fieldwork, analysis and argument is elderly women, or babushkas, in the age (Pearsall 1997; Rosow 1965) by which a Soviet woman had already fulfilled her duties and identities of “a working woman” and “a good mother”. It is a woman’s time that actually was never explicitly addressed by Soviet dominant gender ideology behind well-known cultural representations.
Keywords: babushka; social relations; material recourses; intangible resources